Online/offline preservationists. The material engagement in Syrian cultural heritage between Facebook and offline life - Domenico Copertino (EtnoAntropologia, 2022)
This article follows the activities of a group of Syrian preservationists, that take place both in Facebook and offline. The virtual dimension of social media doesn’t entail the abandonment of the offline dimension of their activism. The latter often involves a struggle against the material changes of structures and the risks the use of forbidden materials (mainly concrete) entails in the heritage sites. The destructions provoked by the current war add to the causes that led Unesco to list the Damascus medina among the heritage sites at risk. The debate about safeguard and transformation of heritage shows the influential role of civil society in Syria and the existence of an area of criticism, admitted by the regime, though in a non-democratic Middle Eastern country.